The importance of ANEEL in the provision of electric energy services in Brazil (Research, Society and Development, 2018)
This work analyzed the effects of the regulatory model on the provision and quality of public services in the electric energy area of Brazil, with ANEEL as the Regulatory Agency. It was evaluated the actions and results of the regulatory model in relation to the adequacy in the provision of public services of electric energy.After the use of this regulatory model, there was an improvement in the adequacy indicators, as well as observed that ANEEL has contributed to the standardization and regulation of the indicators of continuity of electrical energy. After this regulatory process in the provision of electricity services, there was greater efficiency in the sector of electric power distribution, as well as in the legal instruments relating to the concessions and regulation, so much in the economic scope, as in relation to the provision of services.